Novel Chromosomal Mutations Responsible for Fosfomycin Resistance in Escherichia coli - Cattoir, Vincent; Pourbaix, Annabelle; Magnan, Mélanie; Chau, Françoise; de Lastours, Victoire; Felden, Brice; Fantin, Bruno; Guérin, François (Frontiers in Microbiology, 2020)
Fosfomycin resistance in Escherichia coli results from chromosomal mutations or acquisition of plasmid-mediated genes. Because these mechanisms may be absent in some resistant isolates, we aimed at decipher the genetic basis of fosfomycin resistance in E. coli. Different groups of isolates were studied: fosfomycin-resistant mutants selected in vitro from E. coli CFT073 (MIC=1 mg/L) and two groups (wildtype and non-wildtype) of E. coli clinical isolates. Single-nucleotide allelic replacement was performed to confirm the implication of novel mutations into resistance. Induction of uhpT expression by glucose-6-phosphate (G6P) was assessed by RT-qPCR. The genome of all clinical isolates was sequenced by MiSeq. Two first-step mutants were obtained in vitro from CFT073 (MICs, 128 mg/L) with single mutations: G469R in uhpB (M3); F384L in uhpC (M4). Second-step mutants (MICs, 256 mg/L) presented additional mutations: R282V in galU (M7 from M3); Q558* in lon (M8 from M4). Introduction of uhpB or uhpC mutations by site-directed mutagenesis conferred a 128-fold increase in fosfomycin MICs, whereas single mutations in galU or lon were only responsible for a 2-fold increase. Also, these mutations abolished the induction of uhpT expression by G6P. All 14 fosfomycin-susceptible clinical isolates (MICs, 0.5-8 mg/L) were devoid of mutation. At least one genetic change was detected in all but one fosfomycin-resistant clinical isolates (MICs, 32->256 mg/L) including 8, 17, 18, 5, and 8 in uhpA, uhpB, uhpC, uhpT, and glpT genes, respectively. In conclusion, novel mutations in uhpB and uhpC are associated with fosfomycin resistance in E. coli clinical isolates.